DE-cadherin-mediated cell adhesion is essential for maintaining somatic stem cells in the Drosophila ovary - Song, Xiaoqing (National Academy of Sciences, 2002)
Evidence from many systems has shown that stem cells are maintained in “niches” or specific regulatory microenvironments formed by stromal cells. The question of how stem cells are maintained in their niches is important, and further studies will lead to a better understanding of stem cell regulation and enhance the future use of stem cells in regenerative medicine. Here we show that cadherin-mediated cell adhesion is required for anchoring somatic stem cells (SSCs) to their niches in the Drosophila ovary. DE-cadherin and Armadillo/β-catenin accumulate in the junctions between SSCs and their neighboring cells, inner germarial sheath cells. Removal of DE-cadherin from SSCs results in stem cell loss in the adult ovary. Furthermore, the cadherin-mediated adhesion is also important for maintaining SSCs in their niches before adulthood. This study provides further support that SSCs are located in a niche formed by their neighboring cells. We have previously shown that DE-cadherin-mediated cell adhesion is essential for anchoring germ-line stem cells to their niches in the Drosophila ovary. This study further implicates cadherin-mediated cell adhesion as a general mechanism for anchoring stem cells to their niches in a variety of systems.